Tissue diagnosis using power-sharing multifocal Raman micro-spectroscopy and auto-fluorescence imaging - Sinjab, Faris; Kong, Kenny; Gibson, Graham; Varma, Sandeep; Williams, Hywel C.; Padgett, Miles; Notingher, Ioan (Optical Society of America, 2016)
We describe a multifocal Raman micro-spectroscopy detection method based on a digital micromirror device, which allows for simultaneous “power-sharing” acquisition of Raman spectra from ad hoc sampling points. As the locations of the points can be rapidly updated in real-time via software control of a liquid-crystal spatial light modulator (LC-SLM), this technique is compatible with automated adaptive- and selective-sampling Raman spectroscopy techniques, the latter of which has previously been demonstrated for fast diagnosis of skin cancer tissue resections. We describe the performance of this instrument and show examples of multiplexed measurements on a range of test samples. Following this, we show the feasibility of reducing measurement time for power-shared multifocal Raman measurements combined with confocal auto-fluorescence imaging to provide guided diagnosis of tumours in human skin samples.